Economic and Technical Analysis of Utilization Pistia Stratiotes as Magelang Duck Alternative Feed: An Agribusiness Paradigm - Agus Setiadi; Siswanto Imam Santoso; Edjeng Suprijatna; Teysar Adi Sarjana; Suryani Nurfadillah (Buletin Peternakan, 2020)
This study was conducted to determine the economic analysis, performance analysis and chemical quality of the meat of the utilization of pistia stratiotes (PS) in Magelang duck feed. Most duck feed is still very dependent on imports from other countries so there is a need to find alternative feedstuff that are not competing with humans. The experimental research was conducted at the Faculty of Animal Husbandry and Agriculture Undip using 4 treatments, namely T0 duck feed without the addition of PS in feed, T1 added 6% PS in feed, T2 added 12% PS in feed and T3 added 18% PS in duck feed. Parameters observed were final body weight, feed consumption, Feed Conversion Ratio (FCR), mortality, cholesterol, triglycerides, LDL, HDL, antioxidants, feed costs, income over feed costs, return on investment (ROI) and RC ratio. Feed consumption on T3 was the highest. Final body weight on T3 was not significantly different (P> 0.05) compared to T1 and T2 but higher than T0 (P<0.05). The FCR between T3, T2 and T1 was not significantly different (P>0.05), but was lower than T0, duck mortality in this study 0. Blood chemistry analysis (cholesterol, triglycerides, LDL, HDL) showed that T2 and T3 were significantly better than T0 and T1. The results of the economic analysis showed that ducks given PS at T2 and T3 had significant lower feed costs compared to T0 and T1, while ROI from T1, T2 and T3 were significantly higher than T0. The highest IOFC was achieved when duck were fed (T2), while the lowest IOFC was at T0. R/C ratio of T1, T2 and T3 was not significantly different, but higher when compared to T0. Based on the results of technical and economic analysis, the use of PS in 12% duck feed gave the best result of technical and economic performance